Modernization factors for creating corruption awareness through social media and culture - Hussein, Maytham Falih (2021)
Corruption is a global issue and an immense threat to all levels of society. The foundation of corruption is quite a nexus and several promises from the political parties to eliminate corruption is hard. The government of Iraq is also facing corruption on human rights, economic development, and governance due to lack of good governance which in turn elevates the corruption phenomenon. The government still struggles to create people’s awareness about corruption. Therefore, there is a need to conduct a research that focuses on creating such awareness in people. As an initial step toward creating the corruption awareness, this study was geared towards investigating the modernization factors. Hence, Modernization Theory pillared the study in determining the factors deemed fit towards creating people’s awareness about corruption through social media and culture. A conceptual model and seven hypotheses were constructed to guide this study. This research employed a quantitative research method. The data were obtained from a survey through questionnaires, conducted on 320 respondents among students at Baghdad University located in Iraq through online questionnaire. Subsequently, the data were analyzed using Structural Equation Modelling (SEM). The results indicated that modernization factors have a significant relationship towards people’s awareness about corruption. It was because many people have heard about corruption issues, and they need awareness to prevent it. As for modernization factors, the social, economic, political and judiciary were significantly and positively related to people awareness about corruption. Meanwhile, this study also confirmed the mediating roles of culture and social media. The results verified that culture and social media mediated the relationship between modernization factors and people awareness about corruption. This thesis contributes to literature by confirming a conceptual model that is deemed able to explain the causal process of modernization factors towards people awareness about corruption through social media and culture. This study is beneficial for practitioners and policy makers to bring new insight into the relevance of creating people awareness about corruption.